Short-Term Effects of Air Pollution on the Risk of Influenza in Jinan, China during 2020–2021: A Time-Series Analysis - Fangfang Chen; Zhong Liu; Ting Huang; Baoyu Wang; Zhan Sun; Xibao Gao; Weiru Wang (Atmosphere, 2022)
Background: Air pollution leads to many adverse diseases, especially respiratory diseases and cardiac symptoms. However, it has not been studied the association between air pollution and influenza cases in Jinan City, especially during the outbreak of COVID-19; Methods: The data were obtained from China’s Disease Information System, and influenza cases during 2020–2021 in Jinan City were collected from it. We used the generalized additive Poisson model to measure the association between air pollutants and the daily influenza cases after adjusting for possible influence variables; Results: There were 4767 influenza cases. PM2.5 and PM10 on lag 0, lag 3, and lag 4 were significantly associated with an increased risk of influenza; gaseous pollutants (NO2 and SO2) led to higher risk than particulate matter pollutants (PM2.5 and PM10). There were no significant differences for sex subgroup analyses. Except for O3, the incidence risk of males and females was highest on lag 3 and lag 4. For the study of different age groups, influenza cases aged over 59 years had a slightly larger relative risk when exposed to all air pollutants (except O3) than the younger group; Conclusions: The overall number of influenza cases decreased in 2020–2021. PM2.5, SO2, CO, and NO2 were significantly associated with the risk of influenza during 2020–2021. Countermeasures should be developed according to the characteristics of influenza risk to prevent and control it.